Comparison of the Views of Classical Fiqh Ulama and Contemporary Fiqh Ulama on the Use of Zakat Maal for the Development of Educational and Da'wah Institutions - Fikriyah, Khusnul (ZISWAF, 2021)
Nowadays, zakat paid by muzakki is channeled through an educational empowerment model, including scholarships for poor children. In addition to scholarships, the empowerment model also improved, zakat funds are also used for the development of Educational and Da'wah Institutions, including for schools, campuses, dormitories, and mosques. In At-Taubah 60, there is no mention of the Board of Education and Da'wah included in the asnaf who are entitled to receive zakat. Thus, the question arises as to how the legal position of the use of zakat funds for the benefit of the development of educational institutions and da'wah, whether the law is allowed according to sharia or not. This study used a qualitative library research method. The conclusion of this article states that zakat funds are allowed for the construction of educational and da’wah institutions, by using the reason for the "generality of interpretation" of the word sabilillah (في سبيل الله) in At-Taubah: 60 as one of the parties entitled to receive zakat. If the zakat funds for asnaf sabilillah still use the classical meaning, which means only for war, then the scope will be very narrow. In addition, at this time, jihad, which means war on the battlefield no longer exists, because it is considered a violation of human rights, and even if this kind of war is still being financed by the state.